2009
DOI: 10.1111/j.1742-4658.2009.07306.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas aeruginosa nirE gene encodes the S‐adenosyl‐L‐methionine‐dependent uroporphyrinogen III methyltransferase required for heme d1 biosynthesis

Abstract: Biosynthesis of heme d1, the essential prosthetic group of the dissimilatory nitrite reductase cytochrome cd1, requires the methylation of the tetrapyrrole precursor uroporphyrinogen III at positions C‐2 and C‐7. We produced Pseudomonas aeruginosa NirE, a putative S‐adenosyl‐l‐methionine (SAM)‐dependent uroporphyrinogen III methyltransferase, as a recombinant protein in Escherichia coli and purified it to apparent homogeneity by metal chelate and gel filtration chromatography. Analytical gel filtration of puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
3
32
0
1
Order By: Relevance
“…This operon is thought to encode all the enzymes for heme d 1 biogenesis. So far only the function of NirE has been unambiguously determined as an S-adenosylmethionine (AdoMet)-dependent uroporphyrinogen methyltransferase (11,12), a finding that is consistent with previous labeling studies that demonstrate the synthesis of d 1 heme must proceed via precorrin-2 ( Fig. 1 A and C) (13).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…This operon is thought to encode all the enzymes for heme d 1 biogenesis. So far only the function of NirE has been unambiguously determined as an S-adenosylmethionine (AdoMet)-dependent uroporphyrinogen methyltransferase (11,12), a finding that is consistent with previous labeling studies that demonstrate the synthesis of d 1 heme must proceed via precorrin-2 ( Fig. 1 A and C) (13).…”
supporting
confidence: 83%
“…We believe that the oxo groups are formed by the action of NirJ, a radical AdoMet enzyme (20), and that the double bond in the propionate side chain attached to C17 may be mediated by NirF, which, being periplasmic, must catalyze the last step. We have shown that the periplasmic NirF is required for d 1 heme production whereas two other periplasmic proteins (NirC and NirN) coded for in the biogenesis operon are not (11,23). Thus we conclude that NirF catalyzes the final step in d 1 production unless the product of NirF activity is imported to the cytoplasm for further processing, an energetically expensive possibility.…”
Section: Discussionmentioning
confidence: 79%
“…10). Precorrin-2 is a known intermediate in the biosynthesis of siroheme (163,169,170), cobalamin (165,171), coenzyme F 430 (172), and heme d 1 (173,174) ( Fig. 10).…”
Section: Dailey Et Almentioning
confidence: 99%
“…However, what seems to be quite unusual in the nir cluster of T. thermophilus is the absence of homologues to genes putatively implicated in the synthesis of heme d1. As an example, all of the nir clusters thus far described contain a gene (nirE) coding for uroporphyrinogen III methyltransferase (EC 2.1.1.107) (26). Its absence in the cluster of T. thermophilus could be explained by the presence of a homologue in the chromosome of T. thermophilus (TTC0308 in HB27).…”
Section: Discussionmentioning
confidence: 99%